Second Language Acquisition (SLA): Theories of learning English as a second language - Ramazonova , Feruza; Abdurashidova , Sadiya (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article explores the major theories of Second Language Acquisition (SLA) with a particular focus on learning English as a second language. The study examines key theoretical perspectives including behaviorism, nativism, cognitive theory, sociocultural theory, and modern interaction-based approaches. The paper also discusses the role of motivation, age, environment, and psychological factors in the language learning process. By analyzing and comparing these theories, the article highlights their significance for modern language teaching and learning practices. The findings emphasize that successful second language acquisition requires an integrative approach that combines theoretical insights with communicative and learner-centered methods.